THE REALITY OF THE APPLICATION OF ELECTRONIC DOCUMENT MANAGEMENT SYSTEM IN GOVERNMENTAL INSTITUTIONS - AN EMPIRICAL STUDY ON THE PALESTINIAN PENSION AGENCY (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The research aims to identify the status of the application of electronic document management system in governmental institutions - the study was applied on the Palestinian Pension Agency. The population of this study is composed of all employees in the Palestinian Pension Agency. In order to achieve the objectives of the study, the researchers used the descriptive and analytical approach, through which try to describe the phenomenon of the subject of the study, analyze the data and the relationship between the components and the views put around it. Census method was used due to the small size of the study population and ease of access to the target group. (108) questionnaires were distributed to all members of the study population, were (65) employees in the Gaza Strip and (43) employees in the West Bank. All questionnaires were recovered.The study found the following results: There were no statistically significant differences in the members of the population in response to differences in the study about the reality of the application of electronic document management system in governmental institutions - case study on the Palestinian Pension Authority due to the age. There are no statistically significant differences in population members in response to the reality of the application of electronic document management system in governmental institutions - case Study on the Palestinian Pension Authority due to the variable nature of the job. As well as there are no statistically significant differences in the members of the population in response to the study about the reality of the application of electronic document management system in governmental institutions - case study on the Palestinian Pension Authority due to the variable of specialization. There are statistically significant differences in the study about the reality of the application of electronic document management system in governmental institutions - case study on the Palestinian Pension Authority due to Qualification variable for the benefit of members of the population study who are holding a Bachelor degree. There are statistically significant differences in the study about the reality of the application of electronic document management system in governmental institutions - case study on the Palestinian Pension Authority due to the variable number of years of experience for the benefit of members of the study population who have experience between 11-15 years.The study found a group of recommendations, including: the need to focus on the establishment of a general management of electronic documents in the organization structure that takes care of all the technical processes in it an contains scientifically qualified persons in the field of electronic document management. The need is for the attention in developing strategic plans, policies and mechanisms of action commensurate with the electronic document management system.